“Vida cansada”: cotidiano e trabalho no universo mototáxi em Campina Grande-PB. - Timóteo, Anny Glayni Veiga (2014)
In face of the professional diversity found in urban environment, this work disserts on the appeareance and development of a recent socio-professional category - the one of the moto-taxi pilots - focusing on a specific group of moto-taxi pilots in the city of Campina Grande - PB. Subsidized by the etnographic method, this work was developed through participant observation of a moto-taxi stand, between November of 2012 and August of 2013. The stand XXX, located at the Venancio Neiva St. - city downtown, belongs to the "white motorbikes pilots", i.e. the ones that are registered at the city's Traffic and Public Transportation Office (STTP-CG). With the objective of capturing the diverse situations that can be found in the daily lives of those workers, this research listens to what moto-taxi pilots have to say, considering the conditions that drove them to join this system and their relationships with their families, customers, associates, colleagues, employers, companies and public agents. We aimed on perceiving the tensions and conflicts that rise due to the daily relationship between "freedom" - which main representation would justify their stay in such a though job, and the restrictions to their activities, which are commonly associated to the risk intrinsically related with their job, to the urban violence, to traffic regulation, to the embarrassment by the close relationship with the costumer and the stereotypes that those workers are subject to.